PENGARUH PERBANDINGAN BERAT DAN TIGA MEDIA YANG BERBEDA TERHADAP LAJU PERTUMBUHAN INFUSORIA (PARAMECIUM SP) SEBAGAI PAKAN ALAMI LARVA IKAN: The Effect of Comparison of Weight And Three Different Media on The Growth Rate of Infusoria (Paramecium Sp) as Natural Food For Fish Larvae - Syaifullah Syaifullah; Aryani Rahmawati; Kurniawati Kurniawati; Ni Kadek Puji Astuti (Yayasan Al-Amin Qalbu, 2023)
The purpose of this study was to determine the effect of different weights and media on the growth rate of Infusoria (Paramecium sp). The method used in this study is an experimental method using a completely randomized design (CRD). The results of the Variety Sidik Analysis (ANASRA) showed that the growth of Infusoria (Paramecium sp) in each treatment was significantly and very significantly different (Significant) where F count > F table 5% (5.795 > 3.68) and (8.765 > 3.68 ), means that the growth rate of Infusoria (Paramecium sp) is different in each treatment or experiment. The highest cell division was on day V (five) with 5,160 cell divisions and an average of 1,720 cells in the A2B1 treatment and the lowest division occurred on day IX (nine), namely 40 cells with an average of 13.4 cells in treatment A1B3. Further test results using the Least Significant Difference (LSD) test showed a significant (significant) difference in the A2B1 and A2B3 treatments (3,563 > 2,940.452), whereas in the A2B1 and A2B2 treatments (2,563,333 < 2,940,452), A2B2 with A2B3 (1000 < 2940.452), A1B1 with A1B2 (2320 < 2940.452), A1B1 with A1B3 (2780 < 2940.452) and A1B2 with A1B3 (460 < 2940.452) this shows no significant difference (non significant